Design And Construction Of A Web-Based Batak Cultural Product Sales Information System Using The Laravel Framework And Filament Admin - Eva Damayanti Hutagalung; Romanus Damanik (International Journal of Health Engineering and Technology, 2026)
Galeri Ulos Sianipar is a micro, small, and medium enterprise (MSME) engaged in the sale of traditional Batak craft products such as ulos, bags, wallets, and accessories. Previously, conventional transaction and data management processes triggered obstacles such as the risk of data recording errors, reporting delays, and limited marketing reach. This study aims to design and build an integrated web-based Batak cultural sales information system using the Laravel 12 Framework, Filament Admin Panel, and a MySQL database. The system development applies the Waterfall method consisting of the stages of needs analysis, system design, implementation, testing, and maintenance. The results of this study are an e-commerce application that integrates digital catalog features, product management, shopping cart management, checkout processes, digital payment verification (QRIS/Bank Transfer), and real-time financial reports. The implementation of this system has succeeded in simplifying customer access, accelerating the sales administration process, and expanding the reach of digital cultural product promotion.